ANALISIS MINAT SISWI TERHADAP EKSTRAKULIKULER FUTSAL DI SMA N 11 KOTA JAMBI - Muhamad Nurcholis Ramadhan; Reza Hadinata; Anggel hardi yanto (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research aims to analyze female students' interest in futsal extracurricular activities at SMA Negeri 11 Kota Jambi. The declining number of female student participation in this activity in recent years serves as the main background of the study. The research method used is a qualitative approach. Data was collected through in-depth interviews, observations, and documentation, with informant participants consisting of female students who do not participate in futsal extracurricular activities and physical education teachers who also serve as coaches and extracurricular supervisors. The results show that the low interest of female students in futsal extracurricular activities at SMA Negeri 11 Kota Jambi is influenced by several main factors, namely environmental factors, low motivation, physical factors, family influence, and training schedule constraints. Environmental factors include lack of peer participation and discomfort in team dynamics. The low motivation factor is caused by the perception that futsal is less attractive to women and monotonous in training. Physical factors are related to the assumption that futsal is a physically demanding sport that requires high endurance. Additionally, families also play a role in limiting female students' participation by prioritizing academic activities or having the perception that futsal is less suitable for women. Lastly, training schedules that conflict with other activities also contribute to the constraints in female students' participation.